Assessment of quail manure-derived black soldier fly (Hermetia illucens (L.), Diptera Stratiomyidae) frass and its potential in soilless cultivation of tomato (Solanum lycopersicum L.) - Ulson, Bea Niña M. (Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
Hermetia illucens (L.) or black soldier fly (BSF) is known for its ability to reduce multiple organic wastes and produce excrements known as frass. The BSF frass has been studied multiple times as an organic fertilizer for soil medium. However, with the declining health of the world?s soil, it is vital to widen the scope of BSF frass studies on soilless cultivation systems. There is limited knowledge on frass derived from quail manure and its integration with soilless cultivation because studies on BSF frass are relatively few. This study aims to understand how the growth of tomato (Solanum lycopersicum L.) will differ after the amendment of quail manure-derived BSF frass in different cultivation systems. A 30-day greenhouse growth experiment with a control and 7 treatments was conducted following a randomized complete block design. Four BSF frass concentrations, 0 %, 5 %, 15 %, and 25 %, were employed to the garden soil and coconut fiber media. Growth parameters were measured and recorded after the growth experiment. A two-way ANOVA and a Tukey HSD post hoc test were used to analyze the data in RStudio software version 4.2.0. The study found that above optimal values of pH and EC can adversely influence plant growth. Plants grown in soil and 5 % BSF frass concentration showed the highest rate of growth (ROG) and dry biomass. Meanwhile, plants grown in coconut fiber show increasing ROG and dry biomass as BSF frass concentration increases. Lastly, plants grown in coconut fiber show higher values of root-to-shoot ratio and root mass fraction than those grown in soil. The results of this study can be an important contribution to the existing body of knowledge regarding the integration of BSF and soilless cultivation.